Association of child maltreatment and psychiatric diagnosis in Brazilian children and adolescents (Clinics, 2013)
OBJECTIVES: The objective of this study was to evaluate the association between different types of child maltreatment and the presence of psychiatric disorders in highly vulnerable children and adolescents served by a multidisciplinary program. METHODS: In total, 351 patients with a mean age of 12.47, of whom 68.7% were male and 82.1% lived in shelters, underwent psychiatric evaluations based on the Kiddie-Sads-Present and Lifetime Version. Two different methods were used to evaluate maltreatment: medical records were reviewed to identify previous diagnoses related to socioeconomic and psychosocial circumstances, and the Childhood Trauma Questionnaire was used to obtain a structured history of trauma. Bivariate associations were evaluated between psychiatric disorders and evidence of each type and the frequency of abuse. RESULTS: The most frequent psychiatric diagnoses were substance use disorders, affective disorders and specific disorders of early childhood, whereas 13.67% of the sample had no psychiatric diagnosis. All patients suffered neglect, and 58.4% experienced physical or sexual abuse. The presence of a history of multiple traumas was only associated with a diagnosis of substance use disorder. Mental retardation showed a strong positive association with reported physical abuse and emotional neglect. However, a negative correlation was found when we analyzed the presence of a history of multiple traumas and mental retardation. CONCLUSION: All children living in adverse conditions deserve careful assistance, but we found that physical abuse and emotional neglect were most strongly associated with mental retardation and multiple traumas with substance abuse.